2004
DOI: 10.2175/193864704784180370
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Fixed Film Activated Sludge (IFAS) at the Lakeview WWTP The Real Implementation Issues

Abstract: The Lakeview WWTP and Clarkson WWTP in the Region of Peel will be expanded by 2006. The Ontario Ministry of the Environment has indicated its goal to achieve year round nitrification at these facilities. In light of potential benefits in terms of site capacity and capital costs, the Region initiated a demonstration study of the integrated fixed-film activated sludge (IFAS) technology, in order to determine whether full scale implementation of this process is a feasible solution to achieve the new nitrification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
2
6
0
Order By: Relevance
“…The calculated specific nitrification rate of the carriers falls in between 0.2 to 0.5 gN/m 2 .d in the summer, and 0.4 to 0.8 gN/m 2 .d in the winter. The range matches well with values found in the literature measured at the same plant in 2003/04 by Maas et al (2006) and Ross et al (2004), and at other plants (Johnson and McQuarrie (2002); Sen et al (2005)). It can be argued that higher rates in the cold season are a direct result of the assumptions used in the calculation.…”
Section: Comparison Of Treatment Performancesupporting
confidence: 91%
See 2 more Smart Citations
“…The calculated specific nitrification rate of the carriers falls in between 0.2 to 0.5 gN/m 2 .d in the summer, and 0.4 to 0.8 gN/m 2 .d in the winter. The range matches well with values found in the literature measured at the same plant in 2003/04 by Maas et al (2006) and Ross et al (2004), and at other plants (Johnson and McQuarrie (2002); Sen et al (2005)). It can be argued that higher rates in the cold season are a direct result of the assumptions used in the calculation.…”
Section: Comparison Of Treatment Performancesupporting
confidence: 91%
“…They either passed over the screen, or deformed and passed through the screens, and were carried downstream into the final clarifier. To prevent this, screens were enhanced by installing permanent horizontal screens above the vertical screens, and airflows to aiknives were adjusted (Ross et al (2004)). …”
Section: Comparison Of Treatment Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Another full-scale study indicated that IFAS reactor provided more stable ammonia removal at low temperature, sludge settleability was slight increased (Stricker et al, 2007). Studies on sludge production and sludge settling characteristics indicated that IFAS produced less activated sludge with better sludge settling performance than conventional activated sludge (Li et al, 2015;Ross et al, 2004). No obvious difference of sludge settleability was observed between a MLE reactor and an IFAS reactor under different carbon/nitrogen (C/N) ratio and DO concentrations (Sriwiriyarat et al, 2008).…”
Section: Impact Of Solids Retention Time On Particle Size Distributiomentioning
confidence: 99%
“…The plant has shown capabilities of N and P removal (Rutt et al 2006). In Ontario, Canada, the Lakeview Wastewater Treatment Plant has been operating as a full-scale IFAS demonstration project (Stricker et al 2009, Maas et al 2008, Ross et al 2004 since August 2003.…”
Section: Troductiomentioning
confidence: 99%